How we manage haemostasis during sepsis. (3rd March 2019) - Scully, Marie; Levi, Marcel
Summary: Sepsis may be associated with activation of the coagulation system and, in its most severe form, may result in disseminated intravascular coagulation (DIC). Initially, there is thrombosis primarily affecting small and medium sized vessels and contributing to organ dysfunction, but continued activation results in consumption of coagulation factors. This results in prolongation of global coagulation parameters. Often thrombocytopenia is the initial feature in sepsis, which may be followed by prolongation of global coagulation assays, and in severe cases, associated with hypofibrinogenaemia, with overactivation of the fibrinolytic path. The end result is a bleeding phenotype. Scoring systems can be used to help identify patients at risk of DIC and aid in confirming a diagnosis of DIC utilising routine laboratory parameters. Discussion includes medical and blood product support of haemostasis, from thrombotic to bleeding states, in relation to sepsis trigger.